Reabilitação Oral: prótese livre de metal, Removível e implantes. Um caso de 12 anos de acompanhamento - Pellizzer, Eduardo Piza [UNESP]; Mazzaro, José Vitor Quinelli [UNESP]; Santiago Júnior, Joel Ferreira [UNESP]; Verri, Fellippo Ramos [UNESP]; Almeida, Daniel Augusto de Faria [UNESP] (My University, 2013)
The literature has suggested that the association of removable partial dentures with dental implants can improve the quality of life of patients. Thus, the purpose of this study was to present a case report. This case report describes the development of a removable partial denture associated with dental implants bilaterally been monitored for 12 years, and the efficacy of the proposed treatment. The radiographic controls demonstrated no changes on bone tissue. The maxillary arch was rehabilitated with metal-free crowns. The patient was fully satisfied with this technique providing stability, esthetics, and proper function. It was concluded that the technique of using removable partial dentures associated with dental implants is viable and show the advantages of improved function, aesthetics and cost reductions in rehabilitation treatment.

A literatura tem sugerido que a associação de próteses parciais removíveis com implantes osseointegráveis pode melhorar a qualidade de vida dos pacientes. Assim, a proposta deste estudo foi apresentar um caso clínico. Este relato descreveu a elaboração de uma prótese parcial removível associada a implantes osseointegráveis bilateralmente; o acompanhamento durante 12 anos demonstrou eficácia do tratamento proposto. Os controles radiográficos não demonstraram alterações de tecido ósseo. O arco maxilar foi reabilitado com coroas livres de metal. O paciente relatou plena satisfação com a técnica empregada conferindo estabilidade, estética e função adequada. Concluiu-se que a técnica de utilização de próteses parciais removíveis associadas a implantes osseointegráveis é viável e apresenta vantagens de melhoria em função, estética e redução de custos financeiros no tratamento reabilitador.
Oral rehabilitation: metal-free prosthesis, removable prosthesis and dental implants. A twelve-year follow-up case report
Keywords: Dental implants; Biomechanics; Removable partial denture; Metal-free crowns; Implantes dentários; Biomecânica; Prótese parcial removível; Coroas metal-free